(untitled) (Bangladesh Journal of Agriculture, 2023)
The effect of available phosphorus and restriction of feeding on the performance, egg quality, serum biochemical and yolk fatty acid profiles in laying hens at 40 to 60 weeks of age was studied. A total 540 laying hens (Lohmann Brown) aged at 40 weeks were randomly placed in a 2×3 factorial arrangement of dietary treatments including two levels of available phosphorus (AP, 0.32 and 0.45%) and three restricted feeding levels (RFL, 90, 95 and 100%) having 5 replicates in each treatment, and the experiment were conducted for twenty weeks. The results showed that dietary interaction between AP and RFL had significant effects on egg production percentage (P<0.01), egg weight (P<0.05), daily egg mass (P<0.01) and feed conversion ratio (P<0.01). Production performance was significantly (P<0.01) affected by RFL; and both 95% and 100% RFL had showed similar mean value in egg production and egg weight. Egg quality traits: eggshell color and eggshell breaking strength were differed (P<0.05) among the treatments. Moreover, albumen height, Haugh unit and eggshell breaking strength significantly (P<0.05) increased in diet contained 0.45% AP. Dietary limitation of feed did not alter the egg quality except eggshell color. Serum albumin was influenced among the treatments and the mean value of albumin and total protein were same in sole effect of 95% and 100% RFL. Higher serum glucose was obtained in response to the primary effect of 0.32% AP. The total concentration of yolk fatty acid profiles was not assorted in the impacts of AP, RFL and in their interaction. Therefore, the results suggest that 95% feeding was sufficient to hens during second production period, for optimum production performance and egg quality as well as diet containing 0.45% inorganic phosphorus could have influenced positively on egg quality. Bangladesh J. Agri. 2022, 47(2): 119-132